Gulma Inang Virus Tungro dan Kemampuan Penularannya ke Tanaman Padi - Ladja, Fausiah (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Tungro disease in rice (Oryza sativa Linn) is caused by rice tungro virus (RTV), which consists of two forms of particles, namely Rice Tungro Bacilliform Virus and Rice Tungro Spherical Virus. The virus is effectively transmitted by green plant hopper (Nephotettix virescens). The alternate hosts for the virus in the paddy field are the remnant of rice shoot, weeds and wild rice. The research was conducted at green house and at Field Experiment of Virus Research Station in Lanrang South Sulawesi, during Wet Season of 2010. Total of twenty weed species dominant in the rice field were collected and were innoculated with tungro virus. Weed species capable as alternate host of tungro virus were used as source of inoculums for the four rice varieties, i.e. Inpari 7, Inpari 8, IR64, and TNI, and they were planted surrounding the rice test varieties. The experiment was laid in a randomized block design, four replicates. Result showed that among the fifteen weed species identified as alternate host, only four were capable of transmiting tungro virus to rice plant, namely Cyperus rotundus, Phyllanthus niruri, Fimbristylis miliaceae, and Eulisine indica. Tungro disease severity was positively correlated with the population of insect vector.